Epistemological approaches to educational evaluation: between must be and relativity (Foro de Educacion, 2019)
All educational practices require the epistemological delimitation that allows the conceptual understanding and the analysis of its object of study. In the case of educational evaluation – a tool of great use within educational systems worldwide – the theoretical texts that frame its definition and task have left aside the analytical delimitation that underlies its definition and objectives in the educational frame. The current discussions about educational evaluation are strongly focused on their methodological and technical elements that support its activities, and, in some occasions, in the political implications of its use. Under this problem, the present manuscript highlights the need to establish an epistemological positioning of the educational evaluation. Through an analysis of the classical and contemporary theoretical texts of evaluation (particularly those of Spanish speaking) three issues arise of this practice: the concept of educational evaluation itself, the function of the educational evaluation on the delimitation of the educational must be, and the emphasis of this practice in the objectivity of its methods and the conceptualization of its objects of analysis. As a conclusion, the epistemological solidity of its definition is questioned, besides, the need to analyze the basis of the concept of evaluation as well as its goals is highlighted.